Implementation of Lava Lamp Media on Light Material and Properties of Objects in Grade II Elementary Schools - Hitta Alfi Muhimmah; Supriyanto; Mulyani; Suprayitno; Mintohari; Sulistiana Puji Lestari (Indonesia Approach Education, 2023)
This study aims to describe how the implementation of the use of lava lamp media in science learning in grade 2 elementary schools. This study uses a qualitative descriptive method. The flow of this research is to make preparations before implementation, implementation, and analysis of implementation results. Preparation for implementation is carried out by preparing instruments in the form of materials used to make lava lamps and Student Worksheets (LKPD). Implementation is carried out by inviting students to make a lava lamp project and make observations during the manufacturing process, the results of which will be written in the form of writing on the LKPD. Analysis of implementation results is done by reducing data, displaying, and drawing conclusions. Based on data from the results of the analysis of student responses related to the lava lamp media used in science learning on the material of light and the nature of objects, it was found that 95% of students were happy and understood in participating in science learning through the lava lamp media. It can be concluded that the lava lamp media is very suitable for use in learning science in class 2 of States Elementary School IV Lidah Wetan.